KLASIFIKASI BENTUKLAHAN SECARA OTOMATIS MENGGUNAKAN TOPOGRAPHIC POSITION INDEX - Sutanto Trijuni Putro; Nucifera Fitria (Universitas Negeri Semarang, 2017)
Landform is an essential aspect for environmental and disaster studies. Automated landform classification has been developed due to the importance role of landrom for many studies. Automated landform classification can be applied for general purposes.TPI (Topographic Position Index) is one of automated landform classification method. TPI measures the difference between center elevation and mean elevation in its surroundings within certain radius. This study used SRTM data with 90 meters resolution and ASTER GDEM data with 30 meters resolution for the south part of Yogyakarta. Data processing is conducted by using SAGA GIS. The research documented here aims to clarify how TPI support the landform classification thus for practical use can be utilized effectively for analysis any aspect related to landform classification.Generally, automated landform classification for two datas results the same spatial pattern. Study area is mostly classified as plains. But feature number of landform in ASTER GDEM data is larger than STRM data. Because ASTER GDEM data has higher spatial resolution so that the result is more detail. Based on Tobler`s Law, ASTER GDEM work best for 1:50.000 scale, while SRTM fit for 1:180.000 scale.